Ekonomiczne aspekty procesu degradacji i dewastacji gleb - Koczyński, Wojciech (Wydział Prawa i Administracji UAM, 1988)
In the article the author undertakes an attempt to formulate the conception of research into economic consequences of the process of degradation and devastation of rural environment in Poland, especially the degradation and devastationof soil. „Devastation" is understood as the destruction of the layer of soil, and „degradation" is conceived as a gradual loss of its fertility. The considerations have led the author to the conclusion that the most adequate research method is the system analysis; its scheme is included in the article. The said scheme was the basis for multidirectional analysis of relations between the sphere of natural environment and the sphere of human activity. Several types of negative influence of human activity on rural environment, especially on soil, have been taken into account, i.e. detrimental activity connected with industry, agriculture, exchange and consumption. Most of negative influences are reflected in the increase of soil pollution, and — in consequence — in the decrease of arable land area. A separate paper will be devoted to the formulation of a mathematical model of relations between man and environment; the above findings and the scheme will be used for that purpose.
Economic aspects of the process of degradation and devastation of soil